Tingkat Kepuasan Pasien Dalam Pelayanan Kefarmasian Di Apotek Kimia Farma Magetan Tahun 2021 - Yuli Budi Setyono; Rini Sulistyawati; Windadari Murni Hartini (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
The quality of pharmaceutical services must always be raised because they are a crucial component of achieving public health. Patient satisfaction is one factor in service quality. There are still instances of patient complaints, which shows that some services continue to fall short of what patients had hoped for. The purpose of this study is to evaluate the Kimia Farma Magetan Pharmacy's patient satisfaction rate. This study combines descriptive and cross-sectional methods. 180 patients were included in the sampling process utilizing the incidental sampling technique. A questionnaire used as part of the research tool has undergone validity and reliability testing. The results showed that the highest satisfaction was on the assurance dimension while the empathy dimension showed the lowest level of satisfaction. Most of the pharmaceutical service patients are female, namely 56.1%, aged 46-65 years are 64.4% and have a high school education level (High School) of 38.3%. Most of the pharmaceutical service patients at Kimia Farma Magetan Pharmacy have a satisfaction level in the satisfied category of 51.1%.